Generalized Perturbation Theory Based Total Sensitivity and Uncertainty Analysis for High-Fidelity Neutronics Calculation - Ma, Ji; Hao, Chen; Liu, Guanghao; Kang, Le; Li, Peijun; Renteria del Toro, Florencia de los Angeles (Frontiers in Energy Research, 2021)
Neutronics calculation for nuclear reactor with high-fidelity technology can significantly reduce the uncertainties propagated from numerical approximation error and model error. However, the uncertainty of input parameters inevitably exists, especially for nuclear data. On the other hand, resonance self-shielding calculation is essential for multi-group assumption based high-fidelity neutronics calculation, which introduce the implicit effect for calculation responses. In order to fully consider the implicit effects in the process of uncertainty quantification, a generalized perturbation theory (GPT) based implicit sensitivity calculation method is proposed in this paper. Combining the explicit sensitivity coefficient, which can be quantified using classic perturbation theory, the total sensitivity coefficient of calculation responses is obtained Then the total sensitivity and uncertainty module is established in home-developed high-fidelity neutron transport code HNET. To verify the accuracy of the sensitivity calculation methods proposed in this paper, a 2D pin cell problem are used to perform sensitivity analysis and the numerical results show good agreement with results calculated by direct perturbation method. Finally, uncertainty analysis for 2D pin cell problem is performed and some general conclusions are obtained from the numerical results.